Supply-side measures for policy makers to promote mobile broadband coverage - George Houpis; Goran Serdarevic; Jonas Vetterle (International Telecommunications Society (ITS), 2016)
Governments around the world recognise widespread broadband access as a facilitator of economic growth. As a result we observe that many countries have introduced National Broadband Policies which set ambitious targets for broadband coverage. Fixed network may not be commercially viable in more remote rural areas because the cost of roll out is too high. Therefore mobile networks are likely to play an important role in achieving these national targets. In particular, for rural and remote areas of a country where fixed networks are not viable, mobile will likely be the primary form of broadband access. Whilst Governments are interested in maintaining competitive markets there may be some rural areas of a country that are so uneconomic that even mobile network competition may not achieve coverage, either within the required timeframe or at all. It may, however, be desirable for such areas to be covered because of the wider economic benefits of widespread broadband availability. This paper presents and evaluates different forms of supply-side intervention that can be used to achieve mobile broadband coverage in rural areas.
Keywords: 330; Competition Policy; Network Economics; Telecommunications Policy; Economics of Regulation